Smart Fan Temperature and Motion Detection - Rohaidzam, Muhammad Faidz Farhan; Aziz, Roziah (Evolution in Electrical and Electronic Engineering, 2025)
This project is to design and develop a “ the microcontroller temperature based fan speed controller with motion sensor”. This project will present the design, development, control and analysis that can be implemented for home automation system. The home automation system is PIC microcontroller based project which focused on a system to automatically control the speed of a ceiling fan according to the surrounding temperature and the motion sensor detects on human presence. This ceiling fan system and motion sensor contains combination of sensor, controller, driver and motor with integration of embedded controlled programming which means in this case using pic microcontroller as the main controller. This project also presents the expected performance of the automatic fan system and motion sensor, construction of hardware and software development to gather the performance data. Finally, this system performance will be analysed by comparing performance data to the theoretical. End of this project will produce an advance technology with programmable features which control the speed of the fan is depending on the changes in room temperature and the motion sensor detect the presence of a person.